The Role of Islamic Education in Preserving Local Arts and Culture Through Religious Moderation at SMPN 2 Karawang - Nasywa Raisha Putri; Ramaditya Saleh; Ribby Fadilla Aprilia; Salvina Cahya A-Zahra; Abdul Azis (Al-Alim: Jurnal Pendidikan Agama Islam, 2025)
This paper discusses the role of Islamic education in preserving local arts and culture, with a case study at SMPN 2 Karawang Barat. The purpose of this study is to explore the contribution of Islamic education in instilling the values of religious moderation through the preservation of arts and culture. The forms of local cultural preservation include hadroh, marawis, and calligraphy, which function not only as entertainment but also as media for moral and spiritual development, as well as strengthening students’ moderate attitudes. The values of moderation are cultivated through the introduction of Islamic-local cultural acculturation and the reinforcement of tolerance and inclusivity in the learning process. Interviews also revealed several challenges in the current era of modernization, such as the influx of foreign cultures into the archipelago, the high cost of developing traditional arts, and the presence of groups who still hold negative views. However, Islamic education remains fundamentally significant in shaping students’ perspectives toward local culture. This study employs a qualitative approach to understand phenomena directly through experience, using a case study design with the Art and Culture teacher as the key informant and research subject. Data were collected through observation, interviews, and documentation. The findings affirm that Islamic education serves as an effective medium for preserving local culture while simultaneously fostering religious moderation among students.